Do we see the same? Discrepant perception of diversity and diversity management within a company. Issue 3 (25th February 2019) - Bacouel-Jentjens, Sabine; Yang, Inju
Abstract : Purpose: The purpose of this paper is to paper investigates whether different perceptions exist with regard to diversity management within an organisation. Additionally, if such differences exist, what contextual factors influence these perceptions? Design/methodology/approach: The approach of this study is based on inductive and interpretative case research, which aims to compare diverse perceptions in two different organisational units of a company. For this purpose, 30 semi-structured interviews were conducted. Findings: The findings in this paper highlight the importance of contexts in the study of diversity management. That is, contexts such as workforce composition and power (e.g. organisational status) in an organisation as well as the social environment's impact on social identity processes, which results in discrepant focusses on and recognition of diversity management within the same organisation. Research limitations/implications: This study contributes to research on a more nuanced approach to diversity by proposing an importance of contexts for the process of social identity and further perceptual discrepancy. Practical implications: Qualitative research on and findings about perceptual discrepancy help to close the gap between the practice and rhetoric of diversity management. Originality/value: Departing from extant empirical research on diversity at the workplace, which relies predominantly on quantitative methods, a qualitative design of this study allows a refinement of previous findings. Also, this paper provides deeper insight into the sense-making process, resulting in different diversity perceptions by different employees according to their work and social environments or contexts.